The Western Appropriation of Syriac as a "Kabbalistic Language" by Later Christian Kabbalists: New Discoveries and New Perspectives. - Vileno, Anna M. (Aries, 2023)
The article demonstrates that the knowledge of the Syriac language in Western Europe first developed amongst Christian scholars with a strong interest in Kabbalah and that they attributed a mystical dimension to the Syriac language that was not associated with it before. After a survey of the first authors that played a significant role in shaping the appropriation of Syriac as a mystical language (Teseo Ambrogio, Postel, Widmanstetter), I show that the newly discovered last work of Christian Knorr von Rosenroth constitutes the climax of that movement. The study of the later reception of Knorr's work in modern occultism indicates that the Syriac language was eclipsed by the renewed favor of Hebrew language, considered as the magical and mystical language par excellence.